Szklarska Poręba – the Polish highlanders’ imaginarium and the Giant Mountains locality, or, a functional contradiction - Kurpiel, Anna (A mosaic city: The culture-oriented description, 2023)
This article delves into the examination of Szklarska Poręba, a tourist town nestled at the foothills of the Giant Mountains in the region of Lower Silesia, which before the Second World War had been part of German territory and was called Schreiberhau, becoming a part of Poland during the post-war reshaping of borders. The study’s principal objective is to scrutinise practices concerning the complex legacy of a locale steeped in the global-local dynamics of the tourism industry. The paper explores the transplanting of Podhale highlander folklore into the Giant Mountains region, which is interpreted as a spectral continuation of the post-war colonisation of the western territories, as well as the quest for local references and the associated dilemmas of dealing with an inherited, unfamiliar heritage. Based on an analytical review of selected case studies and practices, the concept of “functional contradiction” is introduced, serving as an attempt to articulate and encapsulate the spectrum of phenomena concurrently present in Szklarska Poręba and thus contributing to a broader understanding of cultural dynamics in such settings.